The thermal lens effect on laser heating of a metal nano-sphere particle immersed in oil. (September 2020) - Gurwich, I.; Spector, M.
Highlights: Development of the physical model of beam propagation in thermo-optically nonlinear and non-homogeneous medium. Thermal lensing effect as an origin of saturation and reverse saturation of scattering cross-section of a metal nano-particle. Theoretical validation of intensity dependence of scattering cross-section the heated nano-particle and comparison with the experimental one. Comparison with Mie calculation. Abstract: In this work, we revise the model describing laser heating of a spherical metallic nanoparticle (NP) immersed in transparent oil. We study the generated temperature non-uniformity of the ambient medium and its effect on the propagation of the laser beam. Thus, the model describes the influence of thermal non-uniformity on scattering and absorption of light by the heated particle. Recently, different aspects of the heating of NPs by a laser beam have been actively researched. Some experimental works demonstrated an enigmatic dependence of the effective scattering cross-section of the heated particle on the intensity of the laser beam, illuminating it. The authors of these works labeled the observed effects as "saturation, " and "reverse saturation." In this paper, we show that the propagation of the incident laser beam in a non-uniform oil can by itself be the source of both "saturation" and "reverse saturation" els effects.